2020
DOI: 10.1097/brs.0000000000003835
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Spinal Instability Neoplastic Score for Survival and Ambulatory Function After Surgery for Metastatic Spinal Cord Compression in 110 Patients with Prostate Cancer

Abstract: Study Design.. We retrospectively analyzed Spinal Instability Neoplastic Score (SINS) in 110 patients with prostate cancer operated for metastatic spinal cord compression (MSCC). Objective.. We aimed to investigate the association between SINS and clinical outcomes after surgery for MSCC in patients with prostate cancer. Summary of Background Data.. The SINS is a useful tool for assessing tumor-related spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The results of a retrospective study by Wänman et al also suggested that although SINS is helpful in assessing spinal instability when selecting patients for surgery, it does not predict survival or neurological outcomes. 22 In the present study, thoracic spine metastasis was related to poor postoperative neurological recovery. Chaichana et al also reported a possible significant association between the level of compression and ambulation recovery, with patients with thoracic levels of compression being less likely to regain ambulation, although this asso-ciation did not reach statistical significance in their study (p = 0.07).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The results of a retrospective study by Wänman et al also suggested that although SINS is helpful in assessing spinal instability when selecting patients for surgery, it does not predict survival or neurological outcomes. 22 In the present study, thoracic spine metastasis was related to poor postoperative neurological recovery. Chaichana et al also reported a possible significant association between the level of compression and ambulation recovery, with patients with thoracic levels of compression being less likely to regain ambulation, although this asso-ciation did not reach statistical significance in their study (p = 0.07).…”
Section: Discussionmentioning
confidence: 45%
“…Demographic factors, operative methods, Bilsky grades, Spine Instability Neoplastic Score (SINS), 22 Karnofsky Performance Status (KPS) score, pre-and postoperative motor function grades, pre-and postoperative ambulatory functions, and survival periods of the patients were recorded. The assessment of ambulatory function status considered was that performed 3 months after the operation or, for patients who did not survive for more than 3 months after the surgery, during the last follow-up.…”
Section: Variablesmentioning
confidence: 99%
“…The SINS was designed to support physicians to identify patients who likely benefit from upfront surgery by estimating spinal instability. However, it does not predict neurological outcomes like our new clinical score [ 20 ]. Therefore, the SINS and our new ambulatory score complement each other and should both be used for optimal decision making regarding upfront decompressive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first analysis showing a prognostic role of the Mizumoto score in this distinct group of very old cancer patients. We also could identify the SINS as independent prognosticator for OS, even though the scientific literature regarding the prognostic role of the SINS for OS is heterogeneous and most studied could not link the SINS to survival [ 47 50 ]. As the direct cause of death was not assessable in our study, we cannot prove whether there was a causal link also to disease-free survival.…”
Section: Discussionmentioning
confidence: 99%